Nursing of a patient with insomnia treated by auricular acupoint sticking and pressing combined with stellate ganglion block (耳穴贴压联合星状神经节阻滞治疗失眠1例的护理体会) - WANG Cuiying (王翠英); SUN Lei (孙磊); TANG Ling (唐玲); CHANG Shilei (常石磊); LIU Tianhao (刘天浩); SHEN Hui (申慧); XIE Yindong (解英东); ZHANG Xiangju (张香菊); DONG Wei (董伟) (中西医结合护理)
This article summarized the nursing measures for a patient with insomnia treated by auricular acupoint sticking and pressing combined with stellate ganglion block. Based on nursing risk assessment, emotion care, dietary guidance and other routine nursing measures, the combination treatment of auricular acupoint sticking and pressing and stellate ganglion block was carried out to regulate the flow of blood and qi and dredge the channels and collaterals, relieve symptoms of insomnia and improve the sleeping quality of the patient. (本文总结耳穴贴压联合星状神经节阻滞治疗1例失眠患者的护理经验。在护理评估、情志护理、饮食调护等常规护理的基础上, 开展耳穴贴压联合星状神经节阻滞干预, 通过疏通气血经络, 调节神经系统, 从而改善患者失眠症状, 提高患者睡眠质。)